Bacteriological Quality of Abattoir Effluents Discharged into Water Bodies in Abuja, Nigeria. (19th July 2012) - Nafarnda, W. D.; Ajayi, I. E.; Shawulu, J. C.; Kawe, M. S.; Omeiza, G. K.; Sani, N. A.; Tenuche, O. Z.; Dantong, D. D.; Tags, S. Z.
Abstract : Bacteriological characteristics of abattoir effluents (wastewater), abattoir water source, and water bodies receiving abattoir wastewater were investigated in Abuja, Nigeria using the multiple-tube fermentation technique. Source of water to the abattoirs and the usage of water bodies receiving abattoir effluents were determined using questionnaires. Bacterial counts ranged from 4.8 × 10 6 to 5.8 × 10 5 /100 mL of total coliform (TC), 8.2 × 10 4 to 3.2 × 10 4 /100 mL of Fecal coliform (FC), 5.2 × 10 4 to 2.0 × 10 4 /100 mL of Fecal streptococcus and 1.2 × 10 4 to 2.0 × 10 3 /100 mL of Escherichia coli for abattoir effluents 6.6 × 10 5 to 6.0 × 10 5 /100 mL of TC, 6.2 × 10 4 to 1.8 × 10 4 /100 mL of FC, 1.8 × 10 4 to 6.0 × 10 3 /100 mL of F. streptococcus, and 4.8 × 10 3 to 6.6 × 10 2 /100 mL of E. coli for water bodies receiving abattoir effluents 100 m downstream. TC bacteria counts for abattoir effluents exceeded recommended limit for discharge into surface water in Nigeria. No significant difference (P < 0.05 ) was observed between bacterial counts of abattoir effluents and receiving water bodies 100 m downstream: an indication of contamination of receiving water bodies by abattoir effluents and possible public and environmental health hazards.